Chapter Silvio Pellico's Le mie prigioni: Autobiography versus Religion - Pagliaro, Antonio (Biblioteca di Studi di Filologia Moderna, 2022)
The popularity of Pellico's account among some categories of his contemporaries depends on the nature of his self depiction which nevertheless alienated both Italian patriots and supporters of the status quo. This was a necessary result of the narrator's representation of a religious conversion. The author's literary ambitions remain evident even within this context.